Nonobstructive azoospermia: an etiologic review - Logan Hubbard; Amarnath Rambhatla; Sidney Glina (Asian Journal of Andrology)
Azoospermia is the complete absence of spermatozoa in the ejaculate in two or more semen analyses after centrifugation. Nonobstructive azoospermia (NOA) represents the most severe form of male factor infertility accounting for 10%–15% of cases and stems from an impairment to spermatogenesis. Understanding of the hypothalamic–pituitary–testicular axis has allowed NOA to be subcategorized by anatomic and/or pathophysiologic level. The etiologies of NOA, and therefore, the differential diagnoses when considering NOA as a cause of male factor infertility, can be subcategorized and condensed into several distinct classifications. Etiologies of NOA include primary hypogonadism, secondary hypogonadism, defects in androgen synthesis and/or response, defective spermatogenesis and sperm maturation, or a mixed picture thereof. This review includes up-to-date clinical, diagnostic, cellular, and histologic features pertaining to the multitude of NOA etiologies. This in turn will provide a framework by which physicians practicing infertility can augment their clinical decision-making, patient counseling, thereby improving upon the management of men with NOA.